Electronic and Magnetic Properties of the Interface LaAlO3/TiO2 Anatase from Density Functional Theory. (4th June 2012) - Weissmann, Mariana; Ferrari, V.
Abstract : Ab initio calculations using the local spin density approximation and also including the Hubbard U have been performed for three low-energy configurations of the interface between LaAlO3 and TiO2 anatase. Two types of interfaces have been considered: LaO/TiO2 and AlO2 /TiO, the latter with Ti termination and therefore a missing oxygen. A slab-geometry calculation was carried out, and all the atoms were allowed to relax in the direction normal to the interface. In all the cases considered, the interfacial Ti atom acquires a local magnetic moment, and its formal valence is less than +4. When there are oxygen vacancies, this valence decreases abruptly inside the anatase slab, while in the LaO/TiO2 interface, the changes are more gradual.